2007
DOI: 10.1007/s00431-007-0421-3
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal water loss and cerebral hemodynamics in preterm infants: conventional versus LED phototherapy

Abstract: The aim of our study was to evaluate whether high-intensity gallium nitride light-emitting diode (LED) phototherapy (LPT) influences transepidermal water loss (TEWL) and cerebral hemodynamics in preterm neonates in comparison with conventional phototherapy (CPT). Thirty-one preterm infants were randomized for conventional (n = 14) and for LED (n = 17) phototherapy. All infants were studied using a Tewameter TM 210 and cerebral Doppler ultrasound immediately before phototherapy (time 0), 30 min (time 1), 1-6 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 29 publications
(34 reference statements)
1
34
0
Order By: Relevance
“…Contrary to phototherapy with fluorescent light, LED light therapy does not cause significant transepidermal water loss, because LEDs emit significantly less infrared radiation (18). During routine care of the infants, the average weight gain was 0.7%, independent of light source.…”
Section: Turquoise Vs Blue Led Lightmentioning
confidence: 89%
“…Contrary to phototherapy with fluorescent light, LED light therapy does not cause significant transepidermal water loss, because LEDs emit significantly less infrared radiation (18). During routine care of the infants, the average weight gain was 0.7%, independent of light source.…”
Section: Turquoise Vs Blue Led Lightmentioning
confidence: 89%
“…Bertini and colleagues showed that conventional phototherapy units result in a significant increase of transepidermal water loss in preterm infants, and this side effect was not observed with LED units. [6] Therefore, regarding better safety and efficacy, LED phototherapy seems to be better than conventional phototherapy with halogen or fluorescent light sources in preterm infants, though further studies are required in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, few available reports comparing the efficacy and safety of LED phototherapy with the conventional devices, only two of them used fluorescent tubes, and the results have been controversial. [611] Also, there is no sufficient data for preterm infants in this regard. In this study, we assessed and compared the efficacy and safety of LEDs with fluorescent phototherapy in the treatment of indirect hyperbilirubinemia in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, could reduce duration of treatment and length of hospital stay. (12) LED phototherapy does not appear to have a significant effect on transepidermal water loss and cerebral hemodynamics (13). As LED devices utilize direct current power supply (9,10), they do not usually produce any flickering, a phenomenon that could be related to nausea and dizziness in healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%